FACTORS INFLUENCING SELECTION OF OPEN SOURCE SOFTWARE - shukri, Sakinah mohd; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
In the market of software today, software of open source has emerged as a competitor to proprietary software. In some countries, governments also give support to open source software due to its cost saving aspects and good supportability. The study aimed to enumerate the variables that affect the software of open source selection while comparing with proprietary software in the organizations of Malaysia. Data from different sources have been acquired while focusing primary as well as secondary sources. After the implication of certain techniques and methodologies, results elaborated the variables that significantly affect the software of open source adoption. It is also found that results might not serve as to be expected, where the adoption is somehow relevant to the Malaysian organizations extent.